2016
DOI: 10.3389/fpls.2016.00517
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Roots Grown under Heat Stress Show Global Changes in Their Transcriptional and Proteomic Profiles

Abstract: Heat stress is likely to be a key factor in the negative impact of climate change on crop production. Heat stress significantly influences the functions of roots, which provide support, water, and nutrients to other plant organs. Likewise, roots play an important role in the establishment of symbiotic associations with different microorganisms. Despite the physiological relevance of roots, few studies have examined their response to heat stress. In this study, we performed genome-wide transcriptomic and proteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 53 publications
2
54
0
1
Order By: Relevance
“…From a metabolomic standpoint, we found that several metabolites were downregulated during heat stress, complicating the homeostasis of the general metabolism of the soybean plant. A detailed combined proteomic-transcriptomic study using soybean roots, showed that proteins involved in amino acids, and lipid biosynthesis were severely affected under heat stress [79]. This study corroborates our metabolomics findings in response to heat stress.…”
Section: Discussionsupporting
confidence: 87%
“…From a metabolomic standpoint, we found that several metabolites were downregulated during heat stress, complicating the homeostasis of the general metabolism of the soybean plant. A detailed combined proteomic-transcriptomic study using soybean roots, showed that proteins involved in amino acids, and lipid biosynthesis were severely affected under heat stress [79]. This study corroborates our metabolomics findings in response to heat stress.…”
Section: Discussionsupporting
confidence: 87%
“…Root hairs and stripped roots were isolated after 3 h of incubation as described by Wan et al (2005). This specific time was chosen based on earlier experiments that showed a strong, early transcriptional response to heat treatment after 3 h (Valdes-Lopez et al, 2016). Root hairs and stripped roots were harvested and isolated from two biological replications.…”
Section: Methodsmentioning
confidence: 99%
“…RNA-seq data of root hairs and stripped roots treated with or without heat stress (3 h) were obtained from Valdes-Lopez et al (2016). The raw sequence data were preprocessed using Trimmomatic (0.32) (Bolger et al, 2014) to remove any sequencing adaptors and to trim the low-quality regions of reads.…”
Section: Analysis Of Rna-seq Transcriptomics and Identification Of DImentioning
confidence: 99%
“…japonicus , these CBF TFs participate in short‐term responses to cold stress rather than long‐term responses (Calzadilla et al, ). Also, a study of soybean exposed to heat stress has shown important changes in the expression of genes, including those encoding heat stress factors, AP2/EREBP, MAD box, and WRKY TFs (Valdés‐López et al, ).…”
Section: Transcriptome Dynamics In Legumes Under Abiotic Stressesmentioning
confidence: 99%
“…In addition, a shift in cultivated land use toward legume production can potentially lower the carbon footprint for the production of proteins needed for human consumption, increase N use efficiency, and enhance soil fertility (Considine et al, ; Foyer et al, ; Song et al, ; Sosa‐Valencia et al, ). However, the sustainability of legume crop production is threatened by the increasing incidence of environmental stresses, including persistent drought, increasing soil salinity, heat waves, and soil nutritional deficiencies (Aranjuelo, Cabrerizo, Aparicio‐Tejo, & Arrese‐Igor, ; Kunert et al, ; Maqbool, Aslam, & Ali, ; Nasr Esfahani et al, ; Valdés‐López et al, ; Zhang et al, ). For these reasons, it is essential to intensify legume genetic enrichment programmes, by using advanced breeding approaches and techniques, to develop legume cultivars that possess genetic resilience to environmental stresses.…”
Section: Introductionmentioning
confidence: 99%